Development of dewatering textile materials incorporating slit-pore geometries - Westhaver, Kurt (Environmental technology, 2020)
The use of engineering textile materials has emerged as a viable alternative to conventional methods of sludge dewatering in numerous application areas including municipal wastewater, mining, and pulp and paper. Previous studies have focused on the development of empirical ratios between dewatering performance and the porous properties of the textile material, the challenge is that the latter is difficult to characterize using currently available techniques. In this study, a series of dewatering filters were produced using advanced microfabrication techniques to create well-defined slit-pore geometries; a full-factorial design-of-experiments was employed to evaluate the effects of slit-pore dimensions and slit-pore spacing on the cake layer development and overall dewatering performance in constant-rate dewatering tests with municipal digestate that had been pre-treated with a commercial polymer flocculant. The results from this study provide new insights into the importance of the cake layer in textile dewatering and the impact of textile porosity and flocculation conditions on dewatering performance. It was found that an inverse relationship exists between the porosity of a dewatering fabric and both medium and cake resistances between 0.1% and 1.0% filter porosity, while these properties are comparatively independent of pore structure beyond 1.0%. In addition, the efficacy of the polymer pre-treatment conditions employed was determined to have a substantial impact on solids retention